Cataract surgery in leprosy patients: visual outcomes and complications - Tabassum, Shazia; Kumari, Manisha; Kujur, Alina; Lakra, Marianus Deepak (International Journal of Research in Medical Sciences, 2024)
Background: Objective of study was to study the outcome of cataract surgery in terms of visual results and intra and postoperative complications in case of leprosy patient. Methods: The study analyzed all new cataract cases with leprosy at the outpatient unit, including patients cured of leprosy with senile or complicated cataracts but excluding those with corneal or retinal issues. Small incision cataract surgery was performed, with outcomes and complications assessed. Data collection and analysis utilized descriptive statistics. Follow-ups occurred at discharge and 1-, 4-, and 12-weeks post-surgery, revealing visual acuity ranging from good (6/6-6/18) to poor (<6/60). Results: The study involved 117 eyes from 98 patients (55 males, 43 females, ages 30-89). Pre-surgery, visual acuity was good in 6 eyes (5.12%), borderline in 29 (24.78%), and poor in 82 (70.08%). Post-surgery, 78 eyes (66.67%) had good, 25 (21.37%) borderline, and 10 (8.55%) poor visual acuity. At 12 weeks, 91.14% had good, 5.9% borderline, and 2.95% poor acuity. Common intraoperative issues included posterior capsular rupture in 8 eyes (6.84%), cortical matter loss in 4, iris prolapse in 2, and zonular dehiscence in 1. Early postoperative complications were iridocyclitis in 11 eyes (9.4%) and hyphema in 7 (5.98%), with late complications like chronic anterior uveitis, corneal decompensation, and choroidal detachment occurring in 3 and 2 eyes respectively. Conclusions: Visual outcome was good and the rates of intra and post-operative complications were minimal in our study. Functional vision can be achieved with timely surgical intervention.